2015
DOI: 10.1080/0740817x.2014.953643
|View full text |Cite
|
Sign up to set email alerts
|

Forming competitively balanced teams

Abstract: We examine the problem of assigning individuals to teams so as to make the teams as similar as possible to each other across multiple attributes. This may be complicated by a variety of constraints, including restrictions on whether specific individuals can or should be assigned to the same team. The problem arises in multiple contexts, including youth recreation leagues and academic programs or courses with mandated project groups. We propose a model for the problem and investigate various solution approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The methods used to assign individuals to task performance were found to influence participants’ subsequent procedural and distributive justice perceptions. This finding supports previous research showing that assignment methods can be perceived as having different levels of fairness (Bacon et al., 2001; Knight, 2016; Rubin & Bai, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The methods used to assign individuals to task performance were found to influence participants’ subsequent procedural and distributive justice perceptions. This finding supports previous research showing that assignment methods can be perceived as having different levels of fairness (Bacon et al., 2001; Knight, 2016; Rubin & Bai, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…This study found that random and self-decision assignment methods resulted in higher performance levels than did an ability-based assignment method. This result is in keeping with other team assignment research (Bacon, Stewart, & Silver, 1999; Chapman et al., 2006; Decker, 1995; Miles & Klein, 1998; Rubin & Bai, 2015; Spotts & Chelte, 2005). The result provides further support that using different assignment methods can result in varying levels of subsequent task performance on a short, undesirable task.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Cesani and Steudel [16], Bidanda et al [8], Dimitriadis [19], Becker and Scholl [6,7], Süer et al. [48,49], Süer et al [52], Battaïa and Dolgui [5], Rubin and Bai [42], Otto and Battaïa [38].…”
Section: Introductionmentioning
confidence: 99%